Enabling appropriate personnel skill-mix for progressive realization of equitable access to assistive technology. (4th July 2018) - Smith, Emma M.; Gowran, Rosemary Joan; Mannan, Hasheem; Donnelly, Brian; Alvarez, Liliana; Bell, Diane; Contepomi, Silvana; Ennion (Wegner), Liezel; Hoogerwerf, Evert-Jan; Howe, Tracey; Jan, Yih-Kuen; Kagwiza, Jeanne; et al.
Abstract: Background and Methods: This paper reviews the current capacity of personnel in enabling access to assistive technology (AT) as well as the systems and processes within which they work, and was reviewed, discussed, and refined during and following the Global Research, Innovation, and Education in Assistive Technology (GREAT) Summit. Findings: Key concepts addressed include a person-centred team approach; sustainability indicators to monitor, measure, and respond to needs for service design and delivery; education, research, and training for competent practice, using the six rehab-workforce challenges framework; and credentialing frameworks. We propose development of a competence framework and associated education and training programs, and development and implementation of a certification framework for AT personnel. Conclusions: There is a resolve to address the challenges faced by People globally to access assistive technology. Context specific needs assessment is required to understand the AT Personnel landscape, to shape and strengthen credentialing frameworks through competencies and certification, acknowledging both general and specific skill mix requirements. Implications for Rehabilitation: Personnel in assistive technology (AT) provision should be trained using a person-centred team approach, which emphasizes appropriate skill-mix to address multiple needs within the community. Sustainability indicators should be used which allow personnel to monitor, measure and respond to needs for service design and delivery. A competence framework with associated education and training program, coupled with the development and implementation of a certification framework for AT personnel needs, will promote quality in AT personnel training globally.